A Common Live-Attenuated Avian Herpesvirus Vaccine Expresses a Very Potent Oncogene - Conradie, Andelé M. (mSphere, 2019)
Vaccines play a crucial role in the protection of animals and humans from deadly pathogens. The first vaccine that also protected against cancer was developed against the highly oncogenic herpesvirus Marek’s disease virus (MDV). MDV infects chickens and causes severe immunosuppression, neurological signs, and fatal lymphomas, a process that requires the viral oncogene, meq. The most frequently used Marek’s disease vaccine is the live-attenuated CVI988/Rispens (CVI) strain, which efficiently protects chickens and prevents tumorigenesis. Intriguingly, CVI expresses at least two isoforms of meq; however, it remains unknown to what extent these isoforms contribute to virus attenuation. In this study, we individually examined the contribution of the two CVI-meq isoforms to the attenuation of the vaccine. We inserted the respective isoforms into a very virulent MDV (strain RB-1B), thereby replacing its original meq gene. Surprisingly, we could demonstrate that the longer isoform of meq strongly enhanced virus-induced pathogenesis and tumorigenesis, indicating that other mutations in the CVI genome contribute to virus attenuation. On the contrary, the shorter isoform completely abrogated pathogenesis, demonstrating that changes in the meq gene can indeed play a key role in virus attenuation. Taken together, our study provides important evidence on attenuation of one of the most frequently used veterinary vaccines worldwide. IMPORTANCE Marek’s disease virus (MDV) is one of several oncogenic herpesviruses and causes fatal lymphomas in chickens. The current “gold standard” vaccine is the live-attenuated MDV strain CVI988/Rispens (CVI), which is widely used and efficiently prevents tumor formation. Intriguingly, CVI expresses two predominant isoforms of the major MDV oncogene meq: one variant with a regular size of meq (Smeq) and one long isoform (Lmeq) harboring an insertion of 180 bp in the transactivation domain. In our study, we could break the long-standing assumption that the Lmeq isoform is an indicator for virus attenuation. Using recombinant viruses that express the different CVI-meq isoforms, we could demonstrate that both isoforms drastically differ in their abilities to promote pathogenesis and tumor formation in infected chickens.